Assessing the impact of physician supply inequality on mortality in China: implications for global health - Maomao Cao; Wei Jiang; Run Dong; Yan Chen; Rong Liufu; Li Weng; Bin Du (International Journal for Equity in Health)
Abstract Background Enough supply of physicians plays a vital role in ensuring equitable access to healthcare for residents. This study aims to present a national profile of physician supply and investigate its correlation with all-cause mortality in China. Methods This epidemiological study utilized population-level administrative data. The estimated annual percentage change (EAPC) was calculated to evaluate temporal trends in physician density. The concentration index (CCI) was used to analyze inequalities in physician supply. A generalized estimating equation model and restricted cubic spline were employed to explore the association between physician supply and mortality. Results In China, physician density increased significantly from 23.13 per 10,000 population in 2016 to 30.40 per 10,000 population in 2021, which corresponds to a substantial growth of 23.92% with an EAPC of 5.79% (95% CI: 4.89–6.69). Concurrently, age-standardized all-cause mortality has exhibited a declining trend. The CCI for physician supply remained stable at approximately 0.327. Furthermore, a multivariable generalized estimating equation model and restricted cubic spline analysis demonstrated a strong negative correlation between physician supply and all-cause mortality (R2 = -0.923, P < 0.001). Compared to regions with high physician density, the risk ratios were 1.17 (95% CI: 1.07–1.29) for regions with low physician density, 1.16 (95% CI: 1.07–1.26) for those with lower middle density, and 1.06 (95% CI: 1.00–1.13) for those with upper middle density. Conclusions Regional disparities in physician supply continue to exist, with a gradual narrowing gap within regions. Higher physician supply is associated with reduced all-cause mortality, underscoring the critical importance of equitable physician distribution.